233 Clinical next-generation sequencing pipeline for brca mutations provides traceback to the families of deceased ovarian cancer patients. (18th September 2019) - Mcgee, J; Lin, H; McLachlan, M; Howlett, C; Ainsworth, P; Panabaker, K; Kerkhof, J; Sadikovic, B
Abstract : Objectives: Advances in Next Generation Sequencing (NGS) allow for multiple gene analysis in an efficient, cost-effective manner. Deceased ovarian cancer patients untested for germline BRCA mutations represent a missed opportunity for clinicians to prevent future cancers in their surviving relatives. Families of this lost cohort can benefit through Traceback initiatives. We sought to validate our London Health Sciences custom Hereditary Cancer Panel using formalin fixed paraffin embedded (FFPE) tumor samples to assess BRCA 1/2 status in a cohort of high grade serous ovarian cancer (HGSC) patients. Methods: FFPE samples from 150 deceased HGSC patients were assessed using an Illumina MiSeq sequencer with a mean coverage of 1000x and average minimum coverage of 700x when 24 samples were tested per run. Validation of a subset of identified variants was then undertaken using Sanger and Multiplex Ligation-dependent Probe Amplication (MLPA). Results: Among 150 HGSC samples, we identified 44 samples (29.3%) with reportable variants with variant allele frequencies from 10.3% - 99.4%. These included 35 point mutations/insertions/deletions, 7 exon/whole gene deletions, and 2 BRCA1 exon 13 duplications. A subset (26) of these variants were then confirmed by targeted assays using Sanger and MLPA. Conclusions: Utilizing NGS technology, we reliably identified BRCA mutations in FFPE tumor samples. A validated NGS pipeline provides a valuable clinical tool to conduct Traceback initiatives to the families of deceased ovarian cancer patients never tested for germline mutations.